Historical trends in mortality from “older” vaccine-preventable diseases, Colombia: implications for elimination and control (2022)
Objective: This study aimed to describe the trends in mortality from eight vaccine-preventable diseases in Colombia in the last 40 years and their relationship with vaccination coverage. Study design: It is a population-based descriptive study. Methods: The frequencies of deaths by decade, disease, sex, and the specific mortality rates by age group were calculated. Using a negative binomial regression model, the 10-year changes in mortality and their relationship with vaccination coverage were determined. Results: The number of deaths and the adjusted rates decreased since 1989 in all diseases (incidence rate ratio <1 when compared with the 1979e1988 decade). Vaccination coverage below 90% is associated with an increase in mortality from diphtheria, measles, mumps, neonatal tetanus, and pertussis. Conclusion: Historical changes in mortality support the benefits of vaccination, but new efforts are required to sustain the elimination of diseases.